1995
DOI: 10.1002/jnr.490400503
|View full text |Cite
|
Sign up to set email alerts
|

Interferon γ, interleukin 4 and transforming growth factor β in experimental autoimmune encephalomyelitis in lewis rats: Dynamics of cellular mrna expression in the central nervous system and lymphoid cells

Abstract: The potential role of certain important immunoregulatory and effector cytokines in autoimmune neuroinflammation have been studied. We have examined the expression of mRNA, with in situ hybridization, of interferon gamma (IFN-gamma), interleukin 4 (IL-4) and transforming growth factor beta (TGF-beta) both in sections of spinal cords and the antigen-induced expression of these cytokines by lymphoid cells after stimulation with a dominant encephalitogenic peptide of MBP (MBP 63-88) during the course of actively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(68 citation statements)
references
References 56 publications
3
64
1
Order By: Relevance
“…Issazadeh et al (1995b) found only low numbers of IL-4 mRNA-expressing cells in the spinal cord of rats with EAE. However, in mice, Kennedy et al (1992) found that IL-4 was present in the CNS and reached a peak before the peak of the clinical disease.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Issazadeh et al (1995b) found only low numbers of IL-4 mRNA-expressing cells in the spinal cord of rats with EAE. However, in mice, Kennedy et al (1992) found that IL-4 was present in the CNS and reached a peak before the peak of the clinical disease.…”
Section: Discussionmentioning
confidence: 79%
“…These results may be compared with those of Tanuma et al (1997), who used competitive PCR in a study of cells extracted from the spinal cord of Lewis rats with EAE. We have also presented the results as cytokine mRNA expression per gram of spinal cord (Table 3), which can be compared with the results of Issazadeh et al (1995a) and Issazadeh et al (1995b), who used in situ hybridization to study cytokine mRNA expression per unit area of spinal cord section.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the I1(761)*CA 12 , which is in strong LD with 3 0 (325)*G, was negatively associated with susceptibility to MS in men from USA (cases 52% vs controls 70%, P ¼ 0.022; OR: 0.46, 95% CI: 0.23-0.90). The marker I1(761)*CA n was not associated with MS in the other populations, even after stratifying by gender.…”
Section: Resultsmentioning
confidence: 91%
“…When the populations of men were combined and the analysis was adjusted for populations, carriers for 3 0 (325)*A (P ¼ 0.001; OR: 2.02, 95% CI: 1.31-3.14) and I1(761)*CA 13 (P ¼ 0.034; OR: 1.48, 95% CI: 1.03-2.12) had increased susceptibility to MS. If the effect of the alleles was considered protective, homozygotes for the 3 0 (325)*G (P ¼ 0.001; OR: 0.49, 95% CI: 0.32-0.77) and I1(761)*CA 12 (P ¼ 0.015; OR: 0.58, 95% CI: 0.37-0.90) alleles had reduced susceptibility to MS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation